Payer leverage and hospital compliance with a benchmark: a population-based observational study - DeMonner Sonya; Miller David C; Krein Sarah L; Hollingsworth John M; Hollenbeck Brent K (BMC, 2007)
Abstract Background Since 1976, Medicare has linked reimbursement for hospitals performing organ transplants to the attainment of certain benchmarks, including transplant volume. While Medicare is a stakeholder in all transplant services, its role in renal transplantation is likely greater, given its coverage of end-stage renal disease. Thus, Medicare's transplant experience allows us to examine the role of payer leverage in motivating hospital benchmark compliance. Methods Nationally representative discharge data for kidney (n = 29,272), liver (n = 7,988), heart (n = 3,530), and lung (n = 1,880) transplants from the Nationwide Inpatient Sample (1993 - 2003) were employed. Logistic regression techniques with robust variance estimators were used to examine the relationship between hospital volume compliance and Medicare market share; generalized estimating equations were used to explore the association between patient-level operative mortality and hospital volume compliance. Results Medicare's transplant market share varied by organ [57%, 28%, 27%, and 18% for kidney, lung, heart, and liver transplants, respectively (P < 0.001)]. Volume-based benchmark compliance varied by transplant type [85%, 75%, 44%, and 39% for kidney, liver, heart, and lung transplants, respectively (P < 0.001)], despite a lower odds of operative mortality at compliant hospitals. Adjusting for organ supply, high market leverage was independently associated with compliance at hospitals transplanting kidneys (OR, 143.00; 95% CI, 18.53 - 1103.49), hearts (OR, 2.84; 95% CI, 1.51 - 5.34), and lungs (OR, 3.24; 95% CI, 1.57 - 6.67). Conclusion These data highlight the influence of payer leverage-an important contextual factor in value-based purchasing initiatives. For uncommon diagnoses, these data suggest that at least 30% of a provider's patients might need to be "at risk" for an incentive to motivate compliance.